P-D2 Microscopic detection and localization Of HIV Gp120 epitope exposures on cell-bound virions. (January 2016) - Mengistu, Meron; Lewis, George; Devico, Anthony
Abstract : The pathways of protein domain exposure on the HIV surface delimit relationships between infection and humoral immunity and provide an important framework for developing approaches to treat or prevent HIV infection. The gp120 and gp41 components of HIV envelope trimers have been intensely studied in the context of free virions and it is understood how these proteins must experience multiple structural rearrangements during the course of host cell receptor engagement. However, the impact of such changes on the structural features of an intact virion bound to a host cell remains an ongoing, critical question. Previous predictions held that conserved envelope domains operating within cell contact zones encounter a variety of spatial constraints that occlude their exposure and/or immunoreactivity. Although transition state gp120 domains absent on free virions but induced by CD4 binding (CD4i) are predicted to be profoundly occluded on cell-bound HIV, cognate anti-CD4i antibodies reproducibly mediate ADCC against target cells presenting attached virions. Prompted by such discrepancies, we applied confocal and superresolution microscopic techniques to interrogate virions bound to target cells. Surprisingly, these analyses showed that CD4i epitopes on gp120 are visibly exposed and reactive with whole cognate antibodies on bound virion surfaces for a period of hours. These exposure patterns resemble what is observed for constitutively expressed neutralizing epitopes on cell-bound virions. Further, three-dimensional direct STORM showed that CD4i epitopes were unexpectedly exposed distal to the HIV- cell contact interface in a manner readily accessible to circulating antibodies. Such distal exposures of certain CD4i epitopes was abrogated on mutant virions with aberrant matrix structures. Collectively these observations suggest that previously unsuspected structural dynamics emerge on HIV during host cell attachment. Such processes may provide new windows of vulnerability to antiviral countermeasures.